KONSEP AHL AL-KITAB MENURUT PEMIKIRAN RASYID RIDHA DALAM TAFSIR AL- MANAR - Naila Parah (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2016)
Qur`an as a source of Islamic teachings is actually global precepts; therefore it needs interpretation with continuously reasoning in order to comply with society, which always changes overtime. Interpretation and reasoning to the Qur`an are needed particularly in this modern time. This paper studies Muhammad Rashid Ridha`s thoughts on a term of ahl al-kitab. This paper examines the term of ahl al-kitab in the Qur`an according to him, along with his arguments. With historical approach, Ridha argues that the term of ahl al-kitab refers not only to Nasrani (Christians) or Yahudi (Jews) but also it includes other religions that have a holy book supposedly carried by a prophet